2010
DOI: 10.1210/en.2009-0908
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Stimulates the Release of Gonadotropin-Inhibitory Hormone by the Avian Hypothalamus

Abstract: Gonadotropin-inhibitory hormone (GnIH), a neuropeptide that inhibits gonadotropin synthesis and release, was first identified in quail hypothalamus. GnIH acts on the pituitary and GnRH neurons in the hypothalamus via GnIH receptor to inhibit gonadal development and maintenance. In addition, GnIH neurons express melatonin receptor and melatonin induces GnIH expression in the quail brain. Thus, it seems that melatonin is a key factor controlling GnIH neural function. In the present study, we investigated the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 54 publications
4
97
0
4
Order By: Relevance
“…A regulatory mechanism(s) governing nLPXRFa peptide mRNA expression is essential to understand the physiological significance of novel newt neuropeptides. Recently, we reported that melatonin induces GnIH expression (Ubuka et al 2005) and its release (Chowdhury et al 2010) in the quail brain. Furthermore, we also demonstrated that the expressions of fGRP and fGRP-RPs in the anuran brain are also induced by melatonin .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A regulatory mechanism(s) governing nLPXRFa peptide mRNA expression is essential to understand the physiological significance of novel newt neuropeptides. Recently, we reported that melatonin induces GnIH expression (Ubuka et al 2005) and its release (Chowdhury et al 2010) in the quail brain. Furthermore, we also demonstrated that the expressions of fGRP and fGRP-RPs in the anuran brain are also induced by melatonin .…”
Section: Discussionmentioning
confidence: 99%
“…In both experiments, newts were kept under continuous light. To quantify the newt LPXRFa peptide precursor mRNA, competitive PCR analysis was performed as described previously (Chowdhury et al 2010), with a little modification. The newt brains were removed and snap-frozen immediately in liquid nitrogen.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma LH levels were determined by radioimmunoassay (RIA) using a highly purified chicken LH (USDA-cLH-I-3) 52 as the radioligand and standard, and polyclonal rabbit anti-chicken LH serum (USDA-AcLH-5) 52 supplied by the US Department of Agriculture-Agricultural Research Service (USDA-ARS), Biotechnology and Germplasm laboratory (Beltsville, MD). The RIA was performed as described previously 53,54 . The antiserum against chicken LH, at a final dilution of 1:50,000, exhibited the ability to specifically bind 23% of the added radioligand in the absence of any unlabelled chicken LH.…”
Section: Methodsmentioning
confidence: 99%
“…The effect mechanism of melatonin on reproductive system previously investigated in humans (Balik et al, 2004), other mammals (Tamarkin et al;Uyar & Alan;Yilmaz et al, 2000) and avians (Chowdhury et al, 2010). Melatonin has an inhibitory effect on reproductive system of nonseasonable polyestric animals.…”
Section: Introductionmentioning
confidence: 98%